2020
DOI: 10.3390/cells9071628
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine and Metabotropic Glutamate Receptors Are Present in Blood Serum and Exosomes from SAMP8 Mice: Modulation by Aging and Resveratrol

Abstract: Adenosine (ARs) and metabotropic glutamate receptors (mGluRs) are G-protein coupled receptors (GPCRs) that are modulated in the brain of SAMP8 mice, an animal model of Alzheimer’s disease (AD). In the present work, it is shown the presence of ARs and mGluRs in blood serum and derived exosomes from SAMP8 mice as well as its possible modulation by aging and resveratrol (RSV) consumption. In blood serum, adenosine A1 and A2A receptors remained unaltered from 5 to 7 months of age. However, an age-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…An earlier study has reported that plasma exosomes reflect a similar change in the expression of glutamate receptor with aging as in the brain tissue of transgenic mice. 48 Further, MMKD targeted the suggesting a restoration of glutamate-glutamate receptor signaling, which is critical for long-term potentiation. For example, we observed an increased expression of GRIN1, an obligatory subunit of NMDA type glutamate receptor, while observing a decrease in the GRIN2A and GRIN2B subunits of NMDA receptors and a decrease in AMPA subunit GRIA1.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study has reported that plasma exosomes reflect a similar change in the expression of glutamate receptor with aging as in the brain tissue of transgenic mice. 48 Further, MMKD targeted the suggesting a restoration of glutamate-glutamate receptor signaling, which is critical for long-term potentiation. For example, we observed an increased expression of GRIN1, an obligatory subunit of NMDA type glutamate receptor, while observing a decrease in the GRIN2A and GRIN2B subunits of NMDA receptors and a decrease in AMPA subunit GRIA1.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings suggest that glutamate released by nociceptive neurons may also stimulate PAG and ACC microglial cells, causing the synthesis and release of CatS, a protease that will induce neuronal membrane fractalkine breakdown, generating soluble fractalkine, which, in turn, acts again on the fractalkine receptors of microglial cells, facilitating the synthesis and release of inflammatory mediators that favor neuropathic pain in these supraspinal structures. Hence, considering that polyphenols have been reported to modulate metabotropic glutamate activity in preclinical models 85 , 86 , it can be suggested that polyphenols contained in either GSE or CE may modulate glutamatergic synapses, leading to central sensitization process modulation. Concretely, since the ascending nerve pathway from the spinal cord to the supraspinal structures is a glutamatergic pathway, it would be expected that some of these polyphenols could modulate this glutamatergic neurotransmission of the ascending nociceptive pathway and thus the transmission of action potentials and the reactivation of glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have described that a high-fat diet (HFD) and RSV diet modulate adenosinergic signalling in SAMP8 mice by increasing adenosine A 2 receptors and 5 -NT activity [29]. Interestingly, we found evidence of the presence in serum and exosomes of adenosine A 1 , A 2A , and mGlu5 receptors, and a potential association between brain and serum receptors levels, which were modulated by aging and resveratrol [30] Therefore, the present work aimed to investigate whether cholesterol metabolism was altered by age and RSV supplementation in the brain and blood serum of SAMP8 mice-an animal model of aging and Alzheimer's disease-and their potential link with the amyloidogenic pathway of APP.…”
Section: Introductionmentioning
confidence: 71%
“…Moreover, we have described that a high-fat diet (HFD) and RSV diet modulate adenosinergic signalling in SAMP8 mice by increasing adenosine A 2 receptors and 5′-NT activity [ 29 ]. Interestingly, we found evidence of the presence in serum and exosomes of adenosine A 1 , A 2A , and mGlu5 receptors, and a potential association between brain and serum receptors levels, which were modulated by aging and resveratrol [ 30 ]…”
Section: Introductionmentioning
confidence: 99%